IMPLEMENTASI KEBIJAKAN PROGRAM BEDAH KEMISKINAN RAKYAT SEJAHTERA (BEKERJA) DALAM MENJAMIN KETAHANAN PANGAN MASYARAKAT DI NAGARI LUBUK LAYANG KABUPATEN PASAMAN - Vebi Hanifatun Saleha; Karjuni Dt Maani (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This research is based on the inability of the family to meet food needs. The research objective is to explain the implementation, factors and solutions to overcome the obstacles of the Work Program in Ensuring Food Security of the Nagari Lubuk Layang Pasaman Community. The method in this research is descriptive qualitative. The research was conducted in Nagari Lubuk Layang, Pasaman Regency. Research informants were determined by purposive sampling. Research data obtained from observation, interviews and documentation. The data validity test was done by triangulating the source, then the data was analyzed by reducing, displaying, and drawing conclusions from the research. The research results show that the implementation of the Prosperous People Poverty (Work) Program policy in ensuring community food security has not been carried out properly, because the community still does not know about the Work program in ensuring community food security in Nagari Lubuk Layang, Pasaman Regency. The factors that influence the implementation of the Work Program in ensuring food security for the people in Nagari Lubuk Layang, Pasaman Regency, consist of three factors, namely land ownership, education, income. Furthermore, efforts to overcome these obstacles are to increase public awareness and carry out direct supervision. Keywords: Implementation of policies, Surgery Poverty Prosperous People (Work), Nagari Lubuk Layang.